3D-printed Patient-specific Spine Implants: A Systematic Review. Issue 10 (December 2020) - Wallace, Nicholas; Schaffer, Nathaniel E.; Aleem, Ilyas S.; Patel, Rakesh
Abstract : Study Design: Systematic review. Objective: To review the current clinical use of 3-dimensional printed (3DP) patient-specific implants in the spine. Summary of Background Data: Additive manufacturing is a transformative manufacturing method now being applied to spinal implants. Recent innovations in technology have allowed the production of medical-grade implants with unprecedented structure and customization, and the complex anatomy of the spine is ideally suited for patient-specific devices. Improvement in implant design through the process of 3DP may lead to improved osseointegration, lower subsidence rates, and faster operative times. Methods: A comprehensive search of the literature was conducted using Ovid MEDLINE, EMBASE, Scopus, and other sources that resulted in 1842 unique articles. All manuscripts describing the use of 3DP spinal implants in humans were included. Two independent reviewers (N.W. and N.E.S.) assessed eligibility for inclusion. The following outcomes were collected: pain score, Japanese Orthopedic Association (JOA) score, subsidence, fusion, Cobb angle, vertebral height, and complications. No conflicts of interest existed. No funding was received for this work. Results: A total of 17 studies met inclusion criteria with a total of 35 patients. Only case series and case reports were identified. Follow-up times ranged from 3 to 36 months. Implant types included vertebral body replacement cages, interbody cages, sacral reconstruction prostheses, iliolumbar rods, and a posterior cervical plate. All studies reported improvement in both clinical and radiographic outcomes. 11 of 35 cases showed subsidence >3 mm, but only 1 case required a revision procedure. No migration, loosening, or pseudarthrosis occurred in any patient on the basis of computed tomography or flexion-extension radiographs. Conclusions: Results of the systematic review indicate that 3DP technology is a viable means to fabricate patient-matched spinal implants. The effects on clinical and radiographic outcome measures are still in question, but these devices may produce favorable subsidence and pseudoarthrosis rates. Currently, the technology is ideally suited for complex tumor pathology and atypical bone defects. Future randomized controlled trials and cost analyses are still needed. Level of Evidence: IV—systematic review. Abstract : Supplemental Digital Content is available in the text.